The Phenomenon of Volunteerism in al-Farabi’s Philosophy: The Spiritual Path to Happiness and Virtue - Akhmetova, I.A.; Tutkysheva, G.T. (Karagandy University of the name of acad. E.A. Buketov, 2025)
This article provides a comprehensive analysis of the spiritual essence of volunteerism and its role in achieving happiness within the framework of al-Farabi’s ethical philosophy. Al-Farabi interprets the concept of sa‘āda (happiness) as the highest good attainable through reason, willpower, and the pursuit of virtue. Volunteering is viewed as a conscious moral choice and an expression of one’s inner world and ethical responsibility, carried out through actions that benefit society. The study examines the philosophical parallels between al-Farabi’s views on human spiritual perfection and the ethical foundations of modern volunteer work. Using textual and comparative-philosophical analysis, the article explores how virtuous voluntary acts serve as a pathway to happiness. In Farabi’s thought, happiness is not merely a subjective state but an ontological condition attained through the pursuit of truth, absolute good, and ultimate purpose. This perspective allows for a meaningful re-evaluation of volunteerism as a form of spiritual self-realization and civic contribution. The paper aims to demonstrate the relevance of al-Farabi’s philosophical legacy in addressing contemporary issues of morality, social responsibility, and active citizenship.
Keywords: spiritual perfection; spirituality; intelligence; intelligence; volunteerism; virtue; happiness; evil; good; ethics; al-Farabi